Case Report: GNAQ- and SF3B1 Mutations in an Aggressive Case of Relapsing Uveal Ring Melanoma - Prasuhn, Michelle; Freitag, Josephine Christin; Lüken, Sabine; Kakkassery, Vinodh; Merz, Hartmut; Caliebe, Almuth; Spielmann, Malte; Ranjbar, Mahdy; Rommel, Felix (Frontiers in Oncology, 2022)
The molecular mechanisms for uveal ring melanoma are still unclear until today. In this case report, we describe a patient with a malignant uveal melanoma with exudative retinal detachment that had been treated with plaque brachytherapy resulting in successful tumor regression. After one year, a ring-shaped recurrence with extraocular extension appeared, and the eye required enucleation. Histological and molecular genetic analyses revealed an epithelioid cell type melanoma with complete circumferential involvement of the ciliary body and so far unreported GNAQ and SF3B1 mutations in ring melanoma. Therefore, this report gives new genetic background information on this ocular tumor usually leading to enucleation.